Reaction-time training for elite athletes: A winning formula for champions - Wang, J. (International Journal of Coaching Science, 2009)
Sports skills can be divided into two distinct categories: (1) reaction-time (RT) based sports skills, and (2) non reaction-time based sports skills. RT based sports skills refer to those skills that require athletes take actions based on external stimuli, e.g., upcoming curve ball, opponent's dribbling, striker's shooting, attacker's kick, etc. According to Wang, (2007), shortening RT of responding to external stimuli should be one of the central focuses of high-level training. The purpose of this paper is to: (1) analyze the characteristics of high-level competition, (2) explain how and why RT can positively or negatively affect sports performance at elite level, and (3) provide the specific training strategies of how to shorten RT during competition. The introduced training strategies can be used to maximize athletes' performance in elite competition.